Hubungan Kebiasaan Sarapan Pagi terhadap Prestasi Belajar Siswa Siswi Kelas XII IPA SMA Negeri 8 Tangerang Selatan dan SMA Negeri 4 Tangerang Selatan - Darusafa Ruhmanto; Gaung Eka Ramadhan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Breakfast habits are an important factor in fulfilling nutrition in the morning in order to support health and also support student achievement in school. Even so, many of the children go to school without breakfast. The purpose of this study was to assess the relationship between breakfast habits and student achievement in class XII science. This study used a cross sectional study design from December 2019 to January 2020. A 24-hour Food Recall questionnaire was used to determine breakfast habits. Other factors such as knowledge of nutrition, rest patterns, physical activity and gender were also measured using a questionnaire to support the relationship between variables. Assessment of learning achievement is used by taking the average value of the latest daily test scores with core subjects. The selected sample size is 246 students which are divided into 2 schools. Data were analyzed by computer software. Of the 246 respondents who were divided into 2 schools, there was a significant relationship between breakfast and learning achievement with p < 0.05 for the two schools. The multivariate results of SMA Negeri 8 Tangerang Selatan showed the most dominant physical activity variable with PR (Prevalence Risk) 17,196 and SMA Negeri 4 Tangerang Selatan showed the same result, namely the variable physical activity was the most dominant among other variables with a PR (Prevalence Risk) value of 5,482. Consumption of breakfast that is not regular or not having breakfast has an influence on brain performance in the learning process at school. One of the important factors influencing physical activity is the number of calories for breakfast, nutritional knowledge, rest patterns and gender. Students are expected to practice a healthy breakfast eating pattern with the recommendation of the Nutrition Adequacy Rate (RDA) and regulate physical activity so as not to get tired during school hours.